2020
DOI: 10.1155/2020/1897027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Moderate Physical Exercise on Irisin between Normal Weight and Obese Men

Abstract: Background. Irisin is a myokine that has a beneficial effect on obesity and glucose metabolism by increasing energy expenditure. This study aims to investigate the effect of long-term moderate physical exercise on irisin levels and its correlations with body mass index (BMI), waist circumferences (WC), and metabolic parameters in normal weight and obese males. Material and method. A follow-up case-control study of sixty male participants, comprised of thirty normal weight and thirty obese, who had undergone su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…However, it has recently recognized that irisin can be induced by exercise. Results of our study showed that irisin levels post-EX and at 60 min post-EX were significantly increased than pre-EX irisin levels regardless of exercise intensity, consistent with studies reporting an increase of irisin level after exercise [11,42,43]. Different from previous results…”
Section: Discussionsupporting
confidence: 85%
“…However, it has recently recognized that irisin can be induced by exercise. Results of our study showed that irisin levels post-EX and at 60 min post-EX were significantly increased than pre-EX irisin levels regardless of exercise intensity, consistent with studies reporting an increase of irisin level after exercise [11,42,43]. Different from previous results…”
Section: Discussionsupporting
confidence: 85%
“…Although the relevance to gender is unclear ( Anastasilakis et al, 2014 ; Ruan et al, 2019 ), circulating irisin is shown positive correlated with adiposity indices, such as percent body fat and fat mass ( Jang et al, 2017 ). Notably, a 6-months moderate physical exercise increases the irisin level, decreases body mass index and waist circumferences in obese men ( Rashid et al, 2020 ). Therefore, irisin may be an important factor in maintaining the bone health of obese people.…”
Section: Role Of Exercise In Regulating Chronic Diseasesmentioning
confidence: 99%
“…Considering the results of the studies analyzed in this systematic review and metaanalysis, it seems that long-term physical exercise increases irisin blood levels, especially in obese individuals. More specifically, our study shows that endurance training and combined training increase irisin blood levels in obese older females [26], combined training in obese middle-aged males [33], endurance [46,68] and resistance exercise [49] in young obese adult males, and resistance exercise training in obese older males [52,76]. Moreover, exercise and dietary lifestyle programs demonstrated increases in irisin blood levels in obese children [31], and pelvic floor muscle training increased irisin in obese older females with stress urinary incontinence [80].…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 61%